Information seeking and use behaviour of economists and business analysts - Eric Thivant (Information Research: An International Electronic Journal)
Introduction. The aim of this paper is to deal with the information seeking and use problem in a professional context and understand how activity can influence practices, by taking as examples, the research undertaken by economic analysts. We analyse the relationship between the situational approach, described by Cheuk, the work environment complexity (with social, technological and personal aspects), and the information seeking and use strategies, which relied on Ellis and Wilson's model, with Bates's comments. Method. We interviewed eight economists, using a questionnaire and the SICIA (Situation, Complexity and Information Activity) method. The SICAI method is a qualitative approach, which underlines the relationship between situations, professional contexts and strategies. Both methods allow better understanding of how investment analysts find out what they need for their job. We can clarify their information sources and practices of information seeking, which are very particular because of their activities. We complete our analysis by interviewing analysts from financial institutions. Analysis. A qualitative mode of analysis was used to interpret the interviewees' comments, within the research framework adopted. Results. We find similarity in information seeking and use strategies used by these two groups and environmental levels meet in most situations. But some differences can be also found, explained by the activity frameworks and goals. Conclusion. This study demonstrates that the activity and also the professional context (here the financial context) can directly influence practices.